A case series review of patients with Thrombocytopenia and Absent-Radii syndrome (TARS) and their management during pregnancy - Halperin, Daniel; Pavord, Sue; Myers, Bethan (Clinical Journal of Obstetrics and Gynecology, 2020)
Bleeding diatheses due to platelet-related disorders can present challenges to treating clinicians especially in the context of peri- and post-partum patients in the obstetric setting. TARS is an inherited disorder characterised by reduced bone marrow platelet production, skeletal deformities affecting radii and other limbs; cardiac, renal, and other heterogeneous anomalies may occur. It is caused by co-inheritance of a microdeletion and a nucleotide polymorphism in the RBM8A gene on chromosome 1. Bleeding phenotype is more severe than platelet numbers might predict especially in infants but improves with age. There is minimal literature regarding impact in pregnancy and puerperium. We describe management of three pregnancies in the haematology-obstetrics clinic. As platelet counts normally decrease through pregnancy, close monitoring is required in TAR syndrome. No major bleeding was seen antenatally but two required platelet transfusion during labour. No other treatment definitely improves bleeding, although case reports of steroids claim variable success. Tranexamic acid may be helpful, and thrombopoietin agonists represent a potential future option.